Weaving semiotic engineering in meta-design: A case study analysis. (June 2017) - Fogli, Daniela
Abstract: The work presented in this paper aims at investigating how semiotic engineering and meta-design could be combined to support the development of socio-technical environments that enable End-User Development (EUD). In particular, I investigate the relationships existing between domain experts, playing the role of end-user developers, and meta-designers, mediated by EUD environments, and between end users and end-user developers mediated by EUD products. To this end, three case studies are considered, which belong to the recent research experience in EUD of the author. The case studies are concerned with three different application domains, namely physical prototyping of social products, accumulation and sharing of territory knowledge for first aid intervention, development of e-government services for the citizens of a municipality. The analysis is carried out both on the design process, by adopting a meta-design perspective, and on the product developed in each project, according to a semiotic engineering perspective. The analysis allows to shed light on the human and technical actors involved in EUD and on their communication processes, in order to understand which kinds of interaction visual languages and social conditions should be defined to encourage a continuous user-system co-evolution. As a result, the paper finally proposes some operative indications for the design of systems enabling EUD, which capitalize on semiotic engineering and meta-design ideas.